Temperature dependence of the optical absorption edge of doped gallium arsenide - Chychura, Ig. Iv.; Turianytsia, I. I.; Chychura, Iv. Iv. (Physics and Chemistry of Solid State, 2020)
The temperature dependences of the optical absorption edges of Zn doped GaAs semiconductor crystals have been measured from 300 to 560 K. The temperature dependence of the optical absorption in the Urbach edges is adequately reproduced by a Bose-Einstein model. Analysis of experimental results gave us the opportunity to offer an explicit function of two arguments (photon energy and temperature) for the absorption coefficient of doped crystals in the Urbach edge region.